EDITORIAL - García Laborda, Jesús; Calle Martínez, Cristina; Madarova , Slavka (Encuentro Journal, 2018)
The authors contributing to the Volume 27 of the Encuentro Journal embarked on the journey that has been marked by the previous issues – focusing on the role of teachers as investigators. Contributions included in this issue present educators from various backgrounds reflecting on their teaching practices. Results of their investigation can serve as a stepping-stone towards increasing quality of education and as an inspiration to those who want to improve their teaching.